Geometrical analysis of 3-point linkage of tractors for measurement and display of implement's working depth - P K Pranav; Anmol Kumar; Abhishek Kumar Ansh; Sanjay Kumar (Research in Agricultural Engineering)
The display of the depth of operation on tractors' dashboards facilitates the operator in achieving precise operation. In this study, the depth of operation of a mounted implement was measured and digitally displayed on a tractor's dashboard. The change in depth of operation was sensed by measuring the rotation of the rocker arm of the tractor's hydraulic system. The measured angle of rotation was multiplied by a calibration factor to convert it into the actual depth of operation in centimetres. For the calibration factor, a geometrical analysis of the three-point linkage was carried out, and a mathematical relationship was established based on the length of various linkages and their locations. A computer program was also developed to solve these equations to calculate the calibration factor. The program was validated with six different sizes of three-point linkages and found the maximum root mean square error was within 5%. The developed digital display was evaluated in the laboratory with three different implements and found a maximum error of ± 1 cm. A further evaluation was also carried out in an actual field with implements at three different depth levels, and a deviation of up to ± 13% was found with respect to the manual depth measurement.